The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1161/01.str.14.5.720
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking on regional cerebral blood flow in neurologically normal subjects.

Abstract: SUMMARYThe chronic effects of smoking on regional cerebral blood flow (CBF), and on serum lipids and lipoprotein levels in neurologically normal subjects, were studied. CBF was studied by the 133-Xenon inhalation method and gray matter flow was calculated following the method of Obrist et al. One hundred and eleven subjects, who had no abnormalities in neurological examinations nor in CT scans, were divided into two groups: smokers (37) and non-smokers (74). Those who had a smoking index (Number of cigarettes/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
2
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 23 publications
2
49
2
1
Order By: Relevance
“…Similarly, smokers who smoke ad lib prior to SPECT scanning (including the morning of the scan) have decreased global brain activity compared to former smokers and non-smokers (Rourke et al, 1997). These findings are generally supported by studies using transcranial Doppler ultrasound or the Xe 133 inhalation method to measure responses to smoking, with some (Cruickshank et al, 1989;Kubota et al, 1983Kubota et al, , 1987Rogers et al, 1983), but not all (Kodaira et al, 1993;Terborg et al, 2002), studies showing diminished cerebral blood flow.…”
Section: Brain Activity Responses To Nicotine/cigarette Administrationmentioning
confidence: 90%
“…Similarly, smokers who smoke ad lib prior to SPECT scanning (including the morning of the scan) have decreased global brain activity compared to former smokers and non-smokers (Rourke et al, 1997). These findings are generally supported by studies using transcranial Doppler ultrasound or the Xe 133 inhalation method to measure responses to smoking, with some (Cruickshank et al, 1989;Kubota et al, 1983Kubota et al, , 1987Rogers et al, 1983), but not all (Kodaira et al, 1993;Terborg et al, 2002), studies showing diminished cerebral blood flow.…”
Section: Brain Activity Responses To Nicotine/cigarette Administrationmentioning
confidence: 90%
“…Candidate covariates were selected based on literature review of variables impacting CBF as well as exploratory analyses. Specifically, previous studies have identified relationships between CBF and age (Kubota et al, 1983;Naritomi et al, 1979), gender (Gur et al, 1982), and intima-media thickness (Claus et al, 1996;Nobili et al, 1993). Systolic and diastolic blood pressure, body mass index (BMI), and smoking status were also examined as potential covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic smoking decreases basal cerebral blood flow (Kubota et al, 1983) and increases hematocrit (Isaka et al, 1993), which increases the blood oxygenation level-dependent (BOLD) contrast (Levin et al, 2001). As the fMRI signal in this study is based on BOLD contrasts, group differences in the coupling between neural function and associated increases in cerebral blood could introduce a potential confound for interpretation of BOLD signal change (Jacobsen et al, 2002).…”
Section: Potential Confounds/limitationsmentioning
confidence: 98%